Financial sector development and productivity growth - Subal C. Kumbhakar; George Mavrotas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
Recent years have witnessed important structural changes around the world as a result of the globalization process, the creation of new economic blocks and the liberalization of financial sector in many countries. Responding to these changes many sectors of the industrialized countries have gone through major deregulatory changes to acclimate themselves to new environments. At the same time, many countries have undertaken institutional reforms to build a market-orientated financial system in the hope that transition towards market economy will improve productivity. In the face of uncertainty resulting from changes in regulatory structure and the development of financial institutions to foster market economy, many countries may not be able to achieve their maximum growth potential. In other words, productivity growth is likely to depend on the development of financial institutions and the stage of economic development. That is, a less developed country is likely to benefit more (in terms of output growth rate) from the development of financial institutions than a developed economy with well-developed financial system. In this paper we document this by using data covering 65 countries, varying substantially in terms of level of development and geographic location, and spanning the period 1960-1999. Empirical results obtained from the estimation of two different empirical models regarding the measurement of total factor productivity growth seem to confirm a priori expectations about the overall positive influence of financial systems on productivity in line with previous work on this front. Our results remain robust with respect to alternative definitions of financial sector development we tried.
Keywords: D24; E44; O16; 330; productivity growth; financial sector development; Finanzsektor; Produktivität; Theorie